Nutrient-Loading Mitigation by Shellfish Aquaculture in Semi-Enclosed Estuaries - Guyondet, Thomas; Filgueira, Ramón; Pearce, Christopher M.; Tremblay, Réjean; Comeau, Luc A. (Frontiers in Marine Science, 2022)
Among the services provided by bivalve aquaculture, nitrogen extraction from estuaries is increasingly promoted as these systems are often subject to excess nutrient loading from land activities causing eutrophication symptoms. The ultimate nitrogen extraction service results from the combination of many non-linear interactions between cultured bivalves and the receiving ecosystem. Coupled hydro-biogeochemical modeling was used in a first attempt to integrate all relevant interactions in the assessment of bivalve culture as a nitrogen extraction solution. This potential was evaluated across a range of scenarios including morphology, nutrient loading, aquaculture, and climate change drivers. The model outputs indicate that for all stock scenarios bivalve culture is associated with further retention of material within estuaries. This alteration of the material exchange with the open ocean is not uniform across pelagic variables as it depends on the nature of their interaction with bivalves as well as their own dynamics. When the material extraction resulting from harvest was factored in, however, bivalve culture was showed to provide a net nitrogen removal in the majority of the tested scenarios. In addition, for the husbandry conditions simulated, mussel rather than oyster farming provided the strongest potential for nutrient loading mitigation. Results also support the idea that more open systems are more resilient to change.. Moreover, the mitigation potential was shown to generally increase with bivalve stock biomass. Finally, in future temperature conditions, the mitigation from mussel farms was predicted to increase, while interactions with the oyster reproduction cycle led to reduced harvested biomass and nutrient mitigation potential. This study presents a first quantification of processes, such as bivalve production and material exchange with the open sea, in a dynamic and integrative framework critical to address questions related to eutrophication mitigation.